Break Even Point Analysis of Flower Bucket Business Hellokadoku Payabakung Village, Deli Serdang Regency - Della Chastika; Rara Ivanka; Hasbiyana Haudi Nasution; Dwi Saraswati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of establishing a business is to gain profit or profit that can be used for survival. Likewise with the Flower Bucket Business